Bolivia : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2020)
This paper presents Bolivia's Request for Purchase Under the Rapid Financing Instrument (RFI). Bolivia has requested a purchase under the RFI to cover the urgent balance of payments need arising from an ongoing shift in its terms of trade, slowdown in capital flows, and sudden increase in health care expenditure needs, precipitated by the coronavirus disease 2019 epidemic. The IMF staff assess that Bolivia meets the eligibility requirements for the RFI. Public debt is sustainable, and Bolivia has adequate capacity to repay the IMF. The epidemic will have a substantial impact on Bolivia's economy, constraining domestic output, reducing export demand, lowering the price of its principal exports, curtailing external financing flows, squeezing fiscal revenues, and increasing expenditures for public health and social support. In IMF staff's view, Bolivia's debt remains sustainable over the medium term and, while the outlook remains highly uncertain, Bolivia maintains an adequate capacity to repay the IMF. The IMF staff therefore recommend Board approval of Bolivia's request for a purchase under the RFI of 100 percent of quota.